Long-term prognosis after coronary bifurcation PCI—A nationwide observational study - András Katona; Sacharias von Koch; Pontus Andell; Sebastian Völz; Elmir Omerovic; Ole Fröbert; Moman A. Mohammad (PLoS ONE, 2025)
Background Long-term outcomes of percutaneous coronary intervention (PCI) for bifurcation lesions are underexplored. We investigated long-term PCI outcomes for proximal LAD bifurcation lesions involving D1. Methods Using Swedish registries, we included all patients undergoing LAD-D1 bifurcation PCI with drug-eluting stents between 2010 and 2020. Patients were stratified into two groups: simple PCI and complex PCI. The simple PCI group included those with stents in the proximal LAD only, while complex PCI involved the kissing balloon technique or a 2-stent approach for the proximal LAD and D1. A multivariable Cox regression model was used to estimate event rates of major adverse clinical events (MACE), defined as all-cause death or a new myocardial infarction. Secondary outcomes included target segment revascularization or coronary artery by-pass graft surgery (CABG) and definite stent thrombosis. Results A total of 6,796 individuals were analyzed: 2,007 underwent complex PCI and 4,789 simple PCI. Baseline characteristics were comparable between groups. The complex PCI group was slightly younger, more often male, and more frequently taking statins. At 1-year, MACE rates were lower in the complex PCI group (6.2% vs 7.9%; adjusted HR 0.74, 95% CI 0.59-0.93, p = 0.010). The result was driven by lower all-cause mortality (3.6% vs. 5.0%; adjusted HR 0.73, 95% CI 0.54-0.98, p = 0.036). No significant differences in myocardial infarction, target segment revascularization, CABG, stent thrombosis, stroke, or bleeding were observed between groups, persisting at five years. Conclusion Over a five-year period, complex PCI of LAD/D1 bifurcation lesions was associated with better outcome than simple PCI in a routine clinical setting.